Archaeology, archaeologists and 'Europe' - Pluciennik, Mark
With changes in political structures, a pan-European dimension is increasing in importance for many archaeologists, because of cultural policy and funding from the Council of Europe and, especially, the European Union. Although nationalist frameworks are currently more important, archaeologists should keep a critical eye on European developments.